2010
DOI: 10.1111/j.1540-8159.2010.02848.x
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Cardiac Output Measurement for Optimizing Cardiac Resynchronization Therapy: A Randomized, Blinded, Crossover Study

Abstract: CRT optimization by iterative CO measurements leads to an increase in CO and an improvement of exercise capacity. Our results suggest that this method might become an important additive tool to adjust CRT programming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
6
0
2
Order By: Relevance
“…We believe 6‐MWT improvement to be particularly important as this is a more realistic reflection of the daily activity these patients undergo as compared to a protocol‐driven treadmill test. This confirms the findings of previous studies, which also optimized both AV and VV delay at rest, in showing an important functional improvement in 6‐MWT distance . There was also a significant improvement in echocardiographic dyssynchrony as measured by Ts‐SD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We believe 6‐MWT improvement to be particularly important as this is a more realistic reflection of the daily activity these patients undergo as compared to a protocol‐driven treadmill test. This confirms the findings of previous studies, which also optimized both AV and VV delay at rest, in showing an important functional improvement in 6‐MWT distance . There was also a significant improvement in echocardiographic dyssynchrony as measured by Ts‐SD.…”
Section: Discussionsupporting
confidence: 90%
“…This confirms the findings of previous studies, which also optimized both AV and VV delay at rest, in showing an important functional improvement in 6-MWT distance. 17,18 There was also a significant improvement in echocardiographic dyssynchrony as measured by Ts-SD. In addition, all other trial endpoints-both clinical and echocardiographic-showed improvement also (albeit NS).…”
Section: Resting Crt Optimizationmentioning
confidence: 87%
“…Given the long delay in the delayed response to CRT, it is possible that other factors besides CRT might cause the observed improvement. Several studies have shown that beta‐blocker titration and device programming optimization were associated with improvements in CRT efficacy. However, in our study, we did not find any other possible causes for the delayed response apart from CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Nejsou-li přítomny v plicním řečišti významné AV zkraty, rovná se průtok plícemi minutovému výdeji. Systém byl k optimalizaci stimulačních intervalů použit opakovaně s dobrými výsledky [23][24][25].…”
Section: Neinvazivní Měření Minutového Výdejeunclassified
“…V další tentokrát malé monocentrické dvojitě zaslepené randomizované překřížené studii zahrnující 24 osob se používal k optimalizaci srdeční výdej měřený přístrojem Innocor. Optimální hodnota stimulačních intervalů vedla ke statisticky významně lepší toleranci zátěže [23].…”
Section: Obr 2 -Metoda Výpočtu Optimálního Av Intervalu Podle Meluzínaunclassified